An Investigation on the Janowski Convex Function of Complex Order - Bolcal, Metin; POLATOĞLU, YAŞAR (İstanbul Kültür Üniversitesi Yayınları, 2003)
Bu makalede kompleks mertebeden Janowski konveks fonksiyonları için bazı neticeler veririz.

In this paper we shall give some results for the Janowski convex function of complex order.
Keywords: convex function of complex order; starlike functions of complex order; A.M.S classification (2002) primary 30C45; Karmaşık düzenin dışbükey fonksiyonu; Karmaşık düzenin starlike işlevleri; A.M.S sınıflandırma (2002) birincil 30C45